Young people, creativity and new technologies : the challenge of digital arts - Sefton-Green, Julian (Routledge, 1999)
What is the creative potential of the new technologies? How can computers create new possibilities for artistic and creative work in education?Young People, Creativity and New Technologies describes ways in which ICTs (Information Communication Technologies) can produce new possibilities for creative work both within the formal curriculum and in complementary educational arenas. It provides a series of case studies which show how 'digital arts' are currently being used across school and community arts curricula and demonstrates how ICTs can be used in a genuinely inter-disciplinar.